The platinum coordination complex inhibits cell invasion-migration and epithelial-to-mesenchymal transition by altering the TGF-β-SMAD pathway in colorectal cancer - Abdulla, Maha-Hamadien; Alzailai, Aminah Ahmad; Vaali-Mohammed, Mansoor-Ali; Ahmad, Rehan; Fatima, Sabiha; Zubaidi, Ahmed; Traiki, Thamer bin; Mahmood, Amer; Hamoud Alrashoudi, Reem; Khan, Zahid (Frontiers in Pharmacology, 2023)
There is a steady increase in colorectal cancer (CRC) incidences worldwide; at diagnosis, about 20 percent of cases show metastases. The transforming growth factor-beta (TGF-β) signaling pathway is one of the critical pathways that influence the expression of cadherins allowing the epithelial-tomesenchymal transition (EMT), which is involved in the progression of the normal colorectal epithelium to adenoma and metastatic carcinoma. The current study aimed to investigate the impact of a novel coordination complex of platinum (salicylaldiminato) PT(II) complex with dimethyl propylene linkage (PT-complex) on TGF-β and EMT markers involved in the invasion and migration of the human HT-29 and SW620 CRC cell lines. Functional study and wound healing assay showed PTcomplex significantly reduced cell motility and the migration and invasion of CRC cell lines compared to the untreated control. Western blot performed in the presence and absence of TGF-β demonstrated that PT-complex significantly regulated the TGF-β-mediated altered expressions of EMT markers. PTcomplex attenuated the migration and invasion by upregulating the protein expression of EMTsuppressing factor E-cadherin and suppressing EMT-inducing factors such as N-Cadherin and Vimentin. Moreover, PT-complex significantly suppressed the activation of SMAD3 in both CRC cell lines. Further, the microarray data analysis revealed differential expression of genes related to invasion and migration. In conclusion, besides displaying antiproliferative activity, the PT complex can decrease the metastasis of CRC cell lines by modulating TGF-β-regulated EMT markers. These findings provide new insight into TGF-β/SMAD signaling as the molecular mechanism involved in the antitumoral properties of novel PT-complex.